Peptidomics of Zebrafish Brain in a 6-OHDA-Induced Neurodegeneration Model - Fiametti, Louise O. [UNESP]; de Mello, Felipe Ricardo [UNESP]; de Castro, Leandro M. [UNESP] (Springer Nature, 2024)
Bioactive peptides such as neuropeptides and peptide hormones are largely understood in their involvement in a variety of physiologic systems. In addition to the neuropeptides produced and processed by the classic secretory pathway, intracellular peptides (InPeps) have shown biological activity in studies involving different organisms. A model that has become attractive in many research fields is the zebrafish (Danio rerio), which has allowed correlating behavioral responses or physiological processes with underlying molecular pathways or signaling cascades, improving the understanding of homeostasis mechanisms of the central nervous system, as well as pathological processes such as neurodegenerative diseases. Here, we provide a detailed description of the protocol of treatment with 6-OHDA, which mimics some features of Parkinson’s Disease, as well as the validation of the treatment by evaluation of the locomotor activity and the protocol of peptide extraction followed by isotopic labeling to peptide relative quantitation by mass spectrometry.
Keywords: Danio rerio; Intracellular peptides; Mass spectrometry; Neuropeptide; Parkinson’s Disease; Peptidomics; Zebrafish